Intelligent Computer Graphics 2010 - Plemenos, Dimitri; Miaoulis, Georgios; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Nowadays, intelligent techniques are more and more used in Computer Graphics in order to optimise the processing time, to find more accurate solutions for a lot of Computer Graphics problems, than with traditional methods, or simply to find solutions in problems where traditional methods fail. The purpose of this volume is to present current work of the Intelligent Computer Graphics community, a community growing up year after year. This volume is a kind of continuation of the previously published Springer volumes (3z(BArtificial Intelligence Techniques for Computer Graphics(3y (B(2008) and (3z(BIntelligent Computer Graphics 2009(3y (B(2009). This volume contains selected extended papers from the last 3IA Conference (3IA$1 (B2010), which has been held in Athens (Greece) in May 2010. This year papers are particularly exciting and concern areas like rendering, viewpoint quality, data visualisation, vision, computational aesthetics, scene understanding, intelligent lighting, declarative modelling, GIS, scene reconstruction and other important themes.s
An Introduction to the Bio-logic of Artificial Creatures -- A Cutaway Visualization Technique for Understanding Scenes with Embedded Objects -- Surface Reconstruction with Smart Growing Cells -- Collaborative Foreground Background Object Isolation and Tracking -- Using Fuzzy Logic to Describe Vague Solid Models -- A GIS Platform for Automatic Navigation into Georeferenced Scenes Using GIS Scene Explorer (GIS-SE) -- A Level of Interaction Framework for Exploratory Learning with Characters in Virtual Environments -- A Comparison of Two Machine Learning Approaches for Photometric Solids Compression -- A Collaborative Framework for Virtual Globe Based 3D City Modeling -- A Computerized Method to Generate Complex Symmetric and Geometric Tiling Patterns -- Personalized View Selection of 3D Molecular Proteins -- Interactive Volume-Based Indirect Illumination of Dynamic Scenes.
Keywords: Engineering; Artificial intelligence; Computer graphics; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Computer Graphics